2017
DOI: 10.1242/jeb.148908
|View full text |Cite
|
Sign up to set email alerts
|

Muscles innervated by a single motor neuron exhibit divergent synaptic properties on multiple time scales

Abstract: Adaptive changes in the output of neural circuits underlying rhythmic behaviors are relayed to muscles via motor neuron activity. Presynaptic and postsynaptic properties of neuromuscular junctions can impact the transformation from motor neuron activity to muscle response. Further, synaptic plasticity occurring on the time scale of inter-spike intervals can differ between multiple muscles innervated by the same motor neuron. In rhythmic behaviors, motor neuron bursts can elicit additional synaptic plasticity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Both cpv2a and cpv2b showed response dynamics dominated by facilitation, as is typical for stomach muscles (Govind and Lingle, 1987;Jorge-Rivera et al, 1998;Stein et al, 2006;Blitz et al, 2017). Apart from occasional GAPs, unitary EJPs waveforms, temporal summation, and facilitation in cpv2a were similar to synaptic responses in other pyloric muscles (Govind et al, 1975;Govind and Lingle, 1987;Pulver et al, 2005;Daur et al, 2012).…”
Section: Dynamics Across Spikes Vs Dynamics Across Burstsmentioning
confidence: 57%
See 4 more Smart Citations
“…Both cpv2a and cpv2b showed response dynamics dominated by facilitation, as is typical for stomach muscles (Govind and Lingle, 1987;Jorge-Rivera et al, 1998;Stein et al, 2006;Blitz et al, 2017). Apart from occasional GAPs, unitary EJPs waveforms, temporal summation, and facilitation in cpv2a were similar to synaptic responses in other pyloric muscles (Govind et al, 1975;Govind and Lingle, 1987;Pulver et al, 2005;Daur et al, 2012).…”
Section: Dynamics Across Spikes Vs Dynamics Across Burstsmentioning
confidence: 57%
“…Slower forms of synaptic plasticity like augmentation, post-tetanic potentiation, and long-lasting depression are only apparent with longer lasting and highly repetitive synaptic activation and can depend on a range of cellular phenomena (Regehr and Stevens, 2001;Zucker and Regehr, 2002). Pyloric neuron activity is highly repetitive, and the time constants of recovery from facilitation shown in Figure 4 suggested that dynamics could extend over multiple burst inputs, as has been shown for other stomach muscles (Stein et al, 2006;Blitz et al, 2017). We did not attempt to distinguish between cellular mechanisms that may be involved in dynamics apparent at different timescales, either pre-or postsynaptically.…”
Section: Dynamics Across Bursts Differed Between Cpv2a and Cpv2bmentioning
confidence: 98%
See 3 more Smart Citations